2022
DOI: 10.1109/mis.2020.3040046
|View full text |Cite
|
Sign up to set email alerts
|

Neural Graph for Personalized Tag Recommendation

Abstract: Traditional personalized tag recommendation methods cannot guarantee that the collaborative signal hidden in the interactions among entities is effectively encoded in the process of learning the representations of entities, resulting in insufficient expressive capacity for characterizing the preferences or attributes of entities. In this paper, we firstly propose a graph neural networks boosted personalized tag recommendation model, namely NGTR, which integrates the graph neural networks into the pairwise inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…However, GraphRec adopts a classic GNN framework, i.e., a heavyweight GNN, to aggregate neighborhood information, while our proposed recommendation model aggregates neighbors’ representations by utilizing a lightweight GNN framework that abandons the feature transformation and nonlinear activation components. This finding is consistent with several recommendation models based on lightweight GNNs [ 9 , 29 , 30 ], which show that the feature transformation and nonlinear activation components barely contribute to the recommendation quality.…”
Section: Empirical Analysissupporting
confidence: 91%
“…However, GraphRec adopts a classic GNN framework, i.e., a heavyweight GNN, to aggregate neighborhood information, while our proposed recommendation model aggregates neighbors’ representations by utilizing a lightweight GNN framework that abandons the feature transformation and nonlinear activation components. This finding is consistent with several recommendation models based on lightweight GNNs [ 9 , 29 , 30 ], which show that the feature transformation and nonlinear activation components barely contribute to the recommendation quality.…”
Section: Empirical Analysissupporting
confidence: 91%
“…Furthermore, the aforementioned A-BiLSTM architecture implemented in this research was shown to be highly effective, but with further experimentation with different layer and hyperparameter settings [24][25][26][27][28][29][30][31][32], additional improvements in performance could be made. Evolutionary algorithms [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] could also be exploited pertaining to the above parameter tuning as well as architecture generation processes. Moreover, it would also be beneficial to employ additional medical audio datasets to further evaluate model efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al developed a post-based collaborative filtering method [32] based on a ternary social tag network. To capture higher-order collaborative signals in entity interactions, Yu et al applied graph networks to PITF to aggregate neighbor information from multiple layers to generate the final representation of entity pairs [33]. Wang et al extended PITF by adding weights to user-tag interactions and item-tag interactions separately considering both temporal factors and personalization [34].…”
Section: Related Work a Tag Recommendationmentioning
confidence: 99%